Shifts in the rhizosphere microbiome and exudation profile of avocado (Persea americana Mill.) during infection by Phytophthora cinnamomi and in presence of a biocontrol bacterial strain - Frédérique Reverchon; Mariel García-Meléndez; Edgar Guevara-Avendaño; Oscar Mora-Chávez; Itzel A. Solís-García; Wesley Dáttilo; José A. Guererro-Analco; Alfonso Méndez-Bravo; Juan L. Monribot-Villanueva; Violeta Patiño-Conde; Fernando Pineda-García; Eria A. Rebollar (CABI Agriculture and Bioscience)
Abstract Background Rhizosphere microbiomes are fundamental for plant health, development, and productivity, but can be altered by the incidence of soil-borne pathogens. The dysbiosis (disturbance of the microbiome structure of healthy plants) caused by these pathogens, combined with the recruitment of beneficial microorganisms by the diseased plant, may cause shifts in the rhizosphere microbiome during the infection process. These shifts are likely to be associated with changes in the rhizosphere metabolic profile, as the biochemical dialog, or crosstalk, between host plants and their microbiome is mostly mediated by root exudates. Our objective was to elucidate the shifts in the avocado rhizosphere microbiome and associated changes in the rhizosphere metabolome induced by the infection of the oomycete Phytophthora cinnamomi. We also evaluated the effect of inoculating a bacterial biological control agent (BCA) of P. cinnamomi on the avocado rhizosphere microbiome, in the presence and absence of the pathogen, and on morphological and physiological plant variables, to confirm the potential of the BCA to alleviate the stress induced by the disease. Dataset presentation Here, we present a novel dataset collected from a time-course experiment with four treatments: (1) control trees; (2) trees infected with P. cinnamomi; (3) trees inoculated with the BCA; (4) trees infected with P. cinnamomi and inoculated with the BCA. During the infection process, we measured plant morphological and physiological variables and collected rhizosphere soil samples for bacterial and fungal amplicon sequencing, bacterial RNA-seq and metabolomic analyses. Conclusions Collectively, our data elucidate the shifts in the avocado rhizosphere microbiome after infection by P. cinnamomi and when inoculated with a BCA, and help understand how a pathogen or a beneficial bacterium can alter plant-microbiome crosstalk. Understanding the effect of P. cinnamomi or a BCA on the avocado tree physiology and on the avocado rhizosphere microbiome and metabolome will direct our search for disease biomarkers or potential pathogen antagonists, help identify metabolites related to the recruitment of microorganisms, and assist us in developing integrated disease management strategies.